2021
DOI: 10.23939/mmc2021.04.807
|View full text |Cite
|
Sign up to set email alerts
|

Numerical exploration of mixed convection heat transfer features within a copper-water nanofluidic medium occupied a square geometrical cavity

Abstract: The phenomenon of mixed convection heat transfer in a homogeneous mixture is deliberated thoroughly in this study for cooper-water nanofluids flowing inside a lid-driven square cavity. By adopting the Oberbeck-Boussinesq approximation and using the single-phase nanofluid model, the governing partial differential equations modeling the present flow are stated mathematically based on the Navier--Stokes and thermal balance formulations, where the important features of the scrutinized medium are presumed to remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In comparison with Figure 21, it can be observed that increasing the fractional parameters values, flow characteristics get closer to those of the ordinary fluid flow for both the second-grade and Newtonian-type fluids. e obtained results are compared with the analytical solutions of the flow field presented by the recent studies [23][24][25] which are found to be more compact and simplified. e accuracy of the flow behavior is graphically analysed by setting three decimal places in numerical calculations.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In comparison with Figure 21, it can be observed that increasing the fractional parameters values, flow characteristics get closer to those of the ordinary fluid flow for both the second-grade and Newtonian-type fluids. e obtained results are compared with the analytical solutions of the flow field presented by the recent studies [23][24][25] which are found to be more compact and simplified. e accuracy of the flow behavior is graphically analysed by setting three decimal places in numerical calculations.…”
Section: Resultsmentioning
confidence: 98%
“…Khan [22] studied heat transfer in a thin film of the steady form of flow in touch with the first layer of boundary of porous material in the presence of second-grade fluid. Wakif analysed the analytical and numerical solution of fluid flow with convection heat transfer [23][24][25]. Bhatti et al [26] analysed higher-order slip flow of Eyring-Powell nanofluid for Darcy-Forchheimer in the presence of bioconvection and nonlinear thermal radiation and proved that bioconvection Lewis number declines the microorganism profile while the increasing trend is noted for higher values of slip parameter.…”
Section: Introductionmentioning
confidence: 99%